Ramayana for Children (Hindi) (Noida Om Books, 2022)
Rama, first of the four sons of King Dasharatha, grows up to become a compassionate prince. Smitten by the beauty of Sita, he proves himself worthy of marrying her. As Sita is kidnapped by the demon king Ravana, Rama sets off to Lanka with Hanuman and an army of monkeys to get her back.
Keywords: Religion- Hindu; Hinduism; Ramayana-Hindi